E-Commerce: Perkembangan, Tren, dan Peraturan Perundang-Undangan - Wijaya, Ony (STEKOM PRESS, 2023)
With more people choosing to online shop, e-commerce has become an important part of modern life. This study aims to understand the development of e-commerce and the latest trends, as well as the laws and regulations related to e-commerce business in Indonesia. This study uses a literature study approach by collecting information from various sources such as journals, articles, and books related to this topic. The study results show that e-commerce has experienced rapid development in recent years, with more consumers turning to online shopping and businesses adopting e-commerce business models. Some of the latest trends include the increased use of artificial intelligence (AI) and machine learning, the use of chatbots and virtual assistants, and increased delivery and logistics. However, e-commerce businesses are also faced with a number of challenges and risks, such as online fraud, poor product quality, late delivery, counterfeit brands, and unfair competition.